2019
DOI: 10.1166/jnn.2019.16116
|View full text |Cite
|
Sign up to set email alerts
|

Novel Drug Delivery System Based on Ginsenoside Rb1 Loaded to Chitosan/Alginate Nanocomposite Films

Abstract: Recently, drug delivery using natural and biodegradable nanoparticles has attracted huge attention. This study focused to deliver an anti-cancer and anti-inflammatory drug Ginsenoside Rb1 through chitosan-Alginate nanocomposite film prepared by solution method. Ginsenoside Rb1 is a dammaran saponin group, which is extracted from an herbaceous plant Panax notoginseng. Ginsenoside loaded alginate-chitosan nanocomposite films were characterized by Fourier transform infrared spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…FTIR Spectra. Figure 1 presents the FTIR spectra of AC82L10Rx composite films while the FTIR spectra of CS, AG, LOV, and Rb1 are shown in our previous articles [8,17,[19][20][21][22]; therefore, they were not presented here. From Figure 1, it can be seen that the characteristic peaks of AG, CS, LOV, and ginsenoside Rb1 appeared in the FTIR spectra of AC82L10Rx composite films.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…FTIR Spectra. Figure 1 presents the FTIR spectra of AC82L10Rx composite films while the FTIR spectra of CS, AG, LOV, and Rb1 are shown in our previous articles [8,17,[19][20][21][22]; therefore, they were not presented here. From Figure 1, it can be seen that the characteristic peaks of AG, CS, LOV, and ginsenoside Rb1 appeared in the FTIR spectra of AC82L10Rx composite films.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we prepared and investigated the characteristics, morphology of the AG/CS/LOV composite films, and ability to control in vitro drug release from these composite films [8,[19][20][21][22]. The results indicated that the AG/CS ratio of 4/1 and the LOV content of 10 wt.% (compare with the mass total of AG and CS) were most suitable for preparation of the AG/CS/LOV composite film.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyelectrolyte complexes (PECs) are structured via interactions between polymers possessing oppositely charged groups and are an attractive delivery platform to load water‐soluble or charged molecules such as drugs, proteins, and genes . The complexation behaviors of PECs consisting of counterionic synthetic polymers have been primarily investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is challenging to obtain high loading capability and controlled/desired release of PECs using natural polyelectrolytes. To date, using natural polyelectrolytes, for example, alginate, and chitosan, several approaches to incorporate drug have been developed by layer‐by‐layer coating and using crosslinkers . Herein, we are interested in preparing the complex between counterionic polyelectrolytes without additional crosslinkers and studying fundamental complexation behaviors of PECs and thereof loading release profiles which have been rarely carried out.…”
Section: Introductionmentioning
confidence: 99%